Possible pathways linking ploidy level to cell elongation and cuticular function in hypocotyls of dark-grown Arabidopsis seedlings - Narukawa, Hideki (Plant Signal Behav, 2015)
The mechanisms underlying correlations between ploidy level and cell size in eukaryotes remain unclear. Recently, we showed that cell length was higher in tetraploid than in diploid dark-grown Arabidopsis hypocotyls. Cuticular function was aberrant, and expression of genes of cuticle formation was reduced. Here, the links between cell elongation, cuticular function, and ploidy level in the etiolated hypocotyl were examined. Seedlings defective in cuticle formation exhibited shorter hypocotyls. This was due to inhibition of cell elongation rather than cell proliferation, indicating that the reduced cuticular function was a consequence of tetraploidy-induced cell elongation rather than its cause. Inhibition of hypocotyl elongation by impaired cuticles was lower in tetraploid than diploid, indicating that tetraploid hypocotyls were less sensitive to cuticular damage.